2022
DOI: 10.1002/1873-3468.14322
|View full text |Cite
|
Sign up to set email alerts
|

Screening of novel fungal Carbohydrate Esterase family 1 enzymes identifies three novel dual feruloyl/acetyl xylan esterases

Abstract: Feruloyl esterases (FAEs) and acetyl xylan esterases (AXEs) are important enzymes for plant biomass degradation and are both present in Carbohydrate Esterase family 1 (CE1) of the Carbohydrate‐Active enZymes database. In this study, ten novel fungal CE1 enzymes from different subfamilies were heterologously produced and screened for their activity towards model and complex plant biomass substrates. CE1_1 enzymes possess AXE activity, while CE1_5 enzymes showed FAE activity. Two enzymes from CE1_2 and one from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…The optimum pH (7.5) and temperature (40 °C) of AaFaeD-CD turned out to be similar to those of other cellulolytic enzymes from A. alcalophilum 32 and those of other FAEs in SF5. 9,12,29,31 Here, we have revealed that AaFaeD-CD exerts its enzymatic activity at the highest level at pHs around 7.0−8.5 and temperatures around 40−45 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 71%
See 2 more Smart Citations
“…The optimum pH (7.5) and temperature (40 °C) of AaFaeD-CD turned out to be similar to those of other cellulolytic enzymes from A. alcalophilum 32 and those of other FAEs in SF5. 9,12,29,31 Here, we have revealed that AaFaeD-CD exerts its enzymatic activity at the highest level at pHs around 7.0−8.5 and temperatures around 40−45 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 71%
“… In the ESTHER database, Aa FaeD belongs to the FaeC family . Amino acid sequence alignment for the members of SF5 showed moderate sequence identity of approximately 40–55% between Aa FaeD and 10 previously studied FAEs of ascomycetes species, e.g., Neurospora crassa , Aspergillus niger , Aspergillus sydowii , Aspergillus nidulans , Chrysosporium lucknowense , Chaetomium globulosum , Chaetomium thermophilum , and Corynascus sepedonium (Table S1).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…African elephant; however they did not observe Acidaminococcales. Members of Phascolarctobacterium have been found in the fecal microbiomes of rats and humans and have been positively correlated with an increase in α-linolenic acid in humans (Li et al, 2022) and with being differentially less abundant in rats fed with docosahexaenoic acid (Hosomi et al, 2021). Interestingly, when the rats were fed eicosapentaenoic acid instead of docosahexaenoic acid, the relative abundance of Phascolarctobacterium increased, while the relative abundance of Clostridium (found as one of the main orders in the Budd et al study) decreased.…”
Section: Cazy Familymentioning
confidence: 88%
“…These classes are now respectively included into the following ESTHER families: Type-A in Lipase_3, Type-B in Esterase_phb (PHB depolymerase), Type-C in Tannase, Type-D in FaeC, Type-E in A85-Feruloyl-Esterase, Type-F in BD-FAE. A new distribution of feruloyl esterases based on descriptor-based classification and structural analysis resulted in 13 families [64,65], which are now distributed in ESTHER as SF1,2,3,4,9,10,11 in Tannase, SF5 in FaeC, SF6 Esterase_Phb (CE-1 in the subdivision of CaZy [66]), SF7 Lipase_3, SF8 A85_Feruoyl-esterase, SF12,13 in Fungal_Carb_Lip.…”
Section: Promiscuity Of Enzymatic Reactionmentioning
confidence: 99%